In Silico Study of Ceftaroline’s Molecular Properties - Elso Manuel Cruz Cruz; Eslhey Sánchez Domínguez (Medisur)
Background: Ceftaroline is the latest developed cephalosporin. Its molecular modeling can help deepening the structural bases underpinning its pharmacological characteristics. Objective: to model structural and electronic properties of the ceftaroline. Method: a theoretical study using quantum mechanics methods was conducted in order to model the structure and electronic properties of the ceftaroline. Molecular geometry was optimized with semiempirical calculations according to parameterized model # 3. Molecular properties were calculated according to the Density Functional Theory. Densities of atomic charges and orbital borders were analyzed and compared to the ceftobiprole modeling. Results: the ceftaroline has a more compact and less elongated three-dimensional structure than the ceftobiprole. The positive charges densities on the carbonyl carbon are slightly lower than their equivalents in the ceftobiprole. Conclusions: an ethyl presence in the ceftaroline oxime group modifies its spatial configuration which makes it more compact and may influence its antibacterial action.